Pengaruh Attractiveness,Trustworthiness, Product Price, Terhadap Impulsive Buying Decision Melalui Perceived Enjoyment Sebagai Variabel Antara - Hermanus, Sachiko C.J.; Iskandar, Donant Alananto (Research and Community Service UNIVERSITAS KALBIS, 2025)
This study aims to analyze the influence of Attractiveness, Trustworthiness, and Product price on Perceived enjoyment and its impact on Impulsive buying decision. A quantitative method was employed, with respondents volunteer to be part of the reseach using self-selection sampling. The t-test results indicate that all independent variables have a significant influence on Perceived enjoyment. Furthermore, a simple regression test reveals that Perceived enjoyment significantly affects Impulsive buying decision. The highest mean value indicates that Attractiveness is the dominant factor driving impulsive buying behavior, while the lowest mean value is observed in the Trustworthiness dimension. Managerial implications suggest strengthening visual strategies and enhancing trust elements to improve variable performance. This study provides valuable insights for marketing practitioners and opens opportunities for further exploration of other factors influencing consumer behavior.